Different Types of Curators Based on Field of Work and Responsibilities in OHD Museum - Khoirul Anam; Lono P. Simatupang; Suwarno Wisetrotomo (Institut Seni Indonesia Denpasar, 2022)
The development of curatorial work practices will be very important for the development of museums, arts, and culture. However, it is undeniable that studies and understanding of the development of curatorial work practices are still not optimal in Indonesia. Awareness of the realm and responsibility of the curator is also sometimes poorly understood by the public and the practitioners of curatorial work practices themselves. This vacancy becomes an obstacle in the development of the profession of independent curator and museum curator. Where the curator profession is no longer seen only as a museum guard or seen only as a writer in an exhibition. The discourse in this study will raise the question of how curatorial work practices at OHD Museum are based on the field of work and responsibilities, which we can see from the different types of curators in an art museum. This study focuses on explaining and understanding the definition of curator and the types of the curator in the development of curatorial studies in an art museum. The results of this study indicate that from the division of In-House Curators and Guest Curators at the OHD Museum, they are distinguished by their field of work and responsibilities. The In-House Curators has responsibilities, among others; acquisition, deaccession, borrowing, conservation, restoration, documentation, and research, where related to the field of collection. Then, look at the Guest Curator with responsibilities, among others; creating a curatorial concept for an exhibition, selecting the collections and artists involved, producing a narrative document (curatorial text), and designing an exhibition.